Inflammatory Processes in Complex Regional Pain Syndromes. (May 2013) - Hauser, Joshua; Hsu, Bernard; Nader, Nader D.
<x xml:space="preserve">Abstract</x> Chronic Regional Pain Syndrome, previously known as reflex sympathetic dystrophy, has garnered increased attention in recent years. Many recent studies have attempted to better describe the etiology, pathogenesis, and treatment of symptoms. Despite recent advances to the fund of medical knowledge, the underlying pathophysiology and mechanisms involved in disease progression remain unclear. This review will synthesize and present current theories and data regarding the role of inflammatory cytokines and other mediators in both the central and peripheral nervous systems that contribute to the development and progression of CRPS.